LONG-TERM CARDIOVASCULAR EFFECTS OF COVID-19: A COMPARATIVE STUDY - IMTIAZ , A; KHAN , AA; RAJA , SA; KHAN, SF; AHMED , A; RAHEEL , R (Biological and Clinical Sciences Research Journal, 2023)
The COVID-19 pandemic has left a lasting impact on global health, with increasing evidence of long-term cardiovascular consequences in affected individuals. This study aims to comprehensively investigate and compare the persistent cardiovascular effects of COVID-19 across a diverse population, shedding light on the implications for long-term public health management. The primary objective of this comparative study is to assess and compare the long-term cardiovascular sequelae in COVID-19 survivors across various demographics and disease severities. We seek to understand the extent of cardiovascular involvement, associated risk factors, and outcome variations to inform clinical strategies and public health interventions. We conducted a multi-center retrospective analysis of electronic health records and patient data from diverse geographical regions and demographic groups. Our study involved a large cohort of COVID-19 survivors, categorizing them based on age, sex, comorbidities, and disease severity. We utilized comprehensive cardiovascular assessments, including echocardiography, electrocardiography, and biomarker analysis, to evaluate the cardiovascular status of participants. Our findings revealed long-term cardiovascular effects in COVID-19 survivors, including myocardial injury, arrhythmias, vascular abnormalities, and thrombotic events. These effects varied significantly among different demographic groups and were strongly associated with disease severity and pre-existing comorbidities. Older individuals and those with pre-existing cardiovascular conditions exhibited a higher risk of developing severe cardiovascular complications post-COVID-19. This comparative study underscores the substantial burden of long-term cardiovascular effects in COVID-19 survivors and the need for tailored healthcare interventions. The results emphasize the importance of continuous monitoring and risk assessment, particularly among older adults and individuals with pre-existing cardiovascular conditions. These findings have critical implications for long-term public health management strategies, including vaccination campaigns, prevention programs, and post-COVID-19 care pathways.